Does Information Technology Influence Processes at Universities? - Teacher's Perspective - Mirela Mabic\'; Drazena Gaspar; Daniela Garbin Pranicevic\' (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2022)
The rapid development of information technology (IT) both forces and supports the transformation of universities in almost all their operations (strategic planning, budgeting, education, research, quality control, cooperation with business and society, etc.). The paper presents the research results related to the digitalization of different processes at universities - more specifically, teachers' opinions on the effect of digitalization on different processes. The survey was conducted among the University of Mostar, Bosnia, and Herzegovina (BH) teachers. The authors identified processes at the university and investigated the perceived impact of information technology on them. The findings show that the impact of digitalization is positive on most processes, whereby a strong influence is determined for research projects financed by the Ministry of Education, quality management, teaching, and evaluation of acquired knowledge (examination).
Keywords: I23; L86; O3; 330; information technology; digitalization; process; teachers; university